Credit participation and constranis of the poor in peri-urban areas, Vietnam - A micro-econometric analysis of a household survey - Doan, Tinh (ĐHKT, 2016)
This paper uses a dataset collected from peri-urban areas of Ho Chi Minh City, Vietnam to examine how the poor use their loans, and factors affecting their credit participation and credit constraints. The paper finds that the presence of many commercial banks in the areas does not help the poor, instead the poor rely heavily on informal credit…